Comparison of Antimicrobial Resistance, Virulence Genes, Phylogroups, and Biofilm Formation of Escherichia coli Isolated From Intensive Farming and Free-Range Sheep - Zhao, Xueliang; Lv, Yunyang; Adam, Fathalrhman Eisa Addoma; Xie, Qingfang; Wang, Bin; Bai, Xindong; Wang, Xiaoyuan; Shan, Honghu; Wang, Xinglong; Liu, Haijin; Dang, Ruyi; Wang, Juan; et al. (Frontiers in Microbiology, 2021)
Antibiotic use in wool sheep production is a risk factor for promoting the emergence of resistant E. coli. To ascertain differences in different classes of wool sheep, the antimicrobial resistance, virulence genes, biofilm formation, and phylogroups on 500 E. coli isolates from intensive farming and free-range sheep with diarrheic infections between September 2019 and December 2020 in northwest China were performed. The antimicrobial susceptibility test for 12 classes of antimicrobial agents were determined using broth microdilution susceptibility method, and PCR was used to detect the differences in virulence genes and phylogroups. Additionally, biofilm formation was determined using microtiter plate and slide agglutination methods. Among the 500 E. coli isolates, the majority of the isolates are multidrug resistant (75.4%) and carried at least one virulence genes (94.8%). We observed 412 (82.4%), 360 (72.0%), and 266 (53.2%) are found to be resistant to sulfisoxazole, florfenicol, and tetracyclines respectively. Resistance was also observed to mequindox (46.8%), ampicillin (43.6%), spectinomycin (38.6%), enrofloxacin (34.2%), ceftiofur (21.0%), gentamycin (20.4%), ceftazidime (17.8%), and polymyxin B (7.8%) but no resistance was found to meropenem. These results showed that strains from free-range have fewer antibiotic resistance rather than strains of intensive farming sheep (P<0.05). We observed fifteen virulence genes, of which etrA (n=401, 80.2%) is the most commonly found. In addition, EAEC (86.4%) is dominant among free-range sheep and EHEC (80.1%) is dominant among intensive farming. Among all virulence genes, the strongest correlation was found between etrA and papC gene (P<0.001, OR=455.68). Similarly, the strongest correlation was also found between eltA and sulfisoxazole (P <0.001, OR=877). Furthermore, the majority of the E. coli isolates belonged to phylogroup B1 (50.6%), followed by phylogroup C (20.6%), A (7.4%), E (7.4%), D (5.8%), B2 (1.6%), and F (1%). Interestingly, phylogroup B2 and D were all distributed in intensive farms. In addition, 33 (6.6%), 373 (74.6%) and 94 (18.8%) showed moderate, weakly, and no connection biofilm formation ability, respectively. These data uncovered that wool sheep serves as a reservoir of pathogenic E. coli harboring multiple resistance phenotypes and virulence genes.